Substrate‐Independent Magnetic Bistability in Monolayers of the Single‐Molecule Magnet Dy2ScN@C80 on Metals and Insulators. Issue 14 (24th January 2020) - Krylov, Denis S.; Schimmel, Sebastian; Dubrovin, Vasilii; Liu, Fupin; Nguyen, T. T. Nhung; Spree, Lukas; Chen, Chia‐Hsiang; Velkos, Georgios; Bulbucan, Claudiu; Westerström, Rasmus; Studniarek, Michał; Dreiser, Jan; et al.
Abstract: Magnetic hysteresis is demonstrated for monolayers of the single‐molecule magnet (SMM) Dy2 ScN@C80 deposited on Au(111), Ag(100), and MgO|Ag(100) surfaces by vacuum sublimation. The topography and electronic structure of Dy2 ScN@C80 adsorbed on Au(111) were studied by STM. X‐ray magnetic CD studies show that the Dy2 ScN@C80 monolayers exhibit similarly broad magnetic hysteresis independent on the substrate used, but the orientation of the Dy2 ScN cluster depends strongly on the surface. DFT calculations show that the extent of the electronic interaction of the fullerene molecules with the surface is increasing dramatically from MgO to Au(111) and Ag(100). However, the charge redistribution at the fullerene‐surface interface is fully absorbed by the carbon cage, leaving the state of the endohedral cluster intact. This Faraday cage effect of the fullerene preserves the magnetic bistability of fullerene‐SMMs on conducting substrates and facilitates their application in molecular spintronics. Abstract : Monolayers of Dy2 ScN@C80 exhibit magnetic hysteresis on Au, Ag, and MgO|Ag substrates. The substrates influence the ordering of the endohedral cluster, but do not affect the width of the hysteresis. The carbon cage protects the endohedral magnetic cluster and thus ensures that it sustains magnetic bistability.